2010
DOI: 10.1111/j.1442-2042.2010.02636.x
|View full text |Cite
|
Sign up to set email alerts
|

Harmful gases including carcinogens produced during transurethral resection of the prostate and vaporization

Abstract: Objective: To determine the chemical composition of surgical smoke produced during transurethral resection of the prostate (TURP) and vaporization. Methods: A total of 12 smoke samples were collected from a continuous irrigation suction drainage system to a Tenax absorber at a 0.05 L/min flow rate during TURP and vaporization. The gases were quantitatively and qualitatively analyzed by gas chromatography-mass spectrometry (GC-MS) equipped with a purge and trap sample injector. Results:The main chemical constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
(40 reference statements)
0
27
0
2
Order By: Relevance
“…In the studies of the third category (E4 to E14) (4,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , several gases were identified, but the VOC were the chemical compounds present in all articles. Therefore, the predominant VOC identified and quantified were the following: benzene (4,(21)(22)28) , ethylbenzene (4,21,26,(28)(29) , toluene (4,(21)(22)(23)26,(28)(29)(30) , styrene (4,21,26,28) and butadiene (22,(24)(25)27,30) . This diversity of compounds can be justified by the different types of surgeries in which were collected smoke samples, the body mass index of different patients, and the duration, and energy of electrocautery use because these factors can alter the compounds production (23,26) , increasing the risk of occupational exposure even more, since professionals can work in many surgical rooms and various surgi-www.ee.usp.br/reeusp Composition of the electrocautery smoke: integrative literature review cal procedures daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies of the third category (E4 to E14) (4,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) , several gases were identified, but the VOC were the chemical compounds present in all articles. Therefore, the predominant VOC identified and quantified were the following: benzene (4,(21)(22)28) , ethylbenzene (4,21,26,(28)(29) , toluene (4,(21)(22)(23)26,(28)(29)(30) , styrene (4,21,26,28) and butadiene (22,(24)(25)27,30) . This diversity of compounds can be justified by the different types of surgeries in which were collected smoke samples, the body mass index of different patients, and the duration, and energy of electrocautery use because these factors can alter the compounds production (23,26) , increasing the risk of occupational exposure even more, since professionals can work in many surgical rooms and various surgi-www.ee.usp.br/reeusp Composition of the electrocautery smoke: integrative literature review cal procedures daily.…”
Section: Discussionmentioning
confidence: 99%
“…Harmful gases including carcinogens produced during transurethral resection of the prostate and vaporization (27) 2010 Jeonju, South Korea…”
Section: E11mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the chemical composition of surgical smoke varies by the type of tissue dissected. For example, research has revealed that muscular tissue produces aldehyde and ketone; liver and fatty tissue liberates carbon monoxide and hydrocyanic acid (Barrett & Garber, 2003); epidermal tissue produces xylene, toluene, and ethyl benzene (Barrett & Garber, 2003;Moot et al, 2007;Wu et al, 2011); and prostate resection produces benzene, formaldehyde, carbon monoxide, butadiene, vinyl acetylene, and acrylonitrile (Chung et al, 2010;Weston, Stephenson, Kutarski, & Parr, 2009). Surgical smoke also contains a variety of cellular particles that could cause infections (Alp, Bijl, Bleichrodt, Hansson, & Voss, 2006).…”
Section: Research On the Hazardous Nature Of Surgical Smokementioning
confidence: 99%
“…All chemical levels were below maximum exposure limits, however, CO ware at levels to produce adverse effects to the surgeon. Chung, et al 2010.…”
Section: Cautery Co2 Lasermentioning
confidence: 99%